Rectal syphilis in a HIV patient from Peru - Alcántara Figueroa, Christian (2019)
We present the case of a 53-year-old male patient, a man who had sex with men. He described the presence of inguinal adenopathy and non-painful ulcer with indurated edges on his penis that heal spontaneously after 3 months. In the same period of time the patient presented: tenesmus, bleeding and rectal pain. In the proctoscopy was observed at the level of the rectum: deep ulcer with regular and indurated edges, ulcerated bed with abundant mucus; The rectal mucosa around the ulcer had multiple circumferential erosions 2-4 mm in diameter. The biopsy showed infiltration of lymphomonocollar cells and granulomas. The HIV ELISA test was positive, CD 4: 275 cel./uL, HIV viral load: 10 300 copies / ml, VDRL: Non-reactive, FTA-Abs: 1/10 (positive). Warthin-Starry staining was used in the rectal ulcer biopsy sample identifying spirochetes. After the administration of benzatinic Penicillin G, the symptoms and lesions in the rectal region were resolved. Likewise, antiretroviral treatment was initiated. Ulcerative and erosive proctitis is common in people living with HIV infection, however, it is rare to identify spirochetes in the biopsy sample.